Efficacy of rituximab in systemic manifestations of primary Sjögren's syndrome: results in 78 patients of the AutoImmune and Rituximab registry. Issue 6 (21st December 2012) - Gottenberg, Jacques-Eric; Cinquetti, Gael; Larroche, Claire; Combe, Bernard; Hachulla, Eric; Meyer, Olivier; Pertuiset, Edouard; Kaplanski, Guy; Chiche, Laurent; Berthelot, Jean-Marie; Gombert, Bruno; Goupille, Philippe; et al.
Abstract : Objectives: To evaluate the efficacy and safety of rituximab in patients with primary Sjögren's syndrome (pSS). Methods: The AutoImmune and Rituximab registry has included 86 patients with pSS treated with rituximab, prospectivey followed up every 6 months for 5 years. Results: Seventy-eight patients with pSS (11 men, 67 women), who already had at least one follow-up visit, were analysed. Median age was 59.8 years (29–83), median duration of disease was 11.9 years (3–32). Indications for treatment were systemic involvement for 74 patients and only severe glandular involvement in four patients. The median European Sjögren's Syndrome disease activity index (ESSDAI) was 11 (2–31). 17 patients were concomitantly treated with another immunosuppressant agent. Median follow-up was 34.9 months (6–81.4) (226 patient-years). Overall efficacy according to the treating physician was observed in 47 patients (60%) after the first cycle of rituximab. Median ESSDAI decreased from 11 (2–31) to 7.5 (0–26) (p<0.0001). Median dosage of corticosteroid decreased from 17.6 mg/day (3–60) to 10.8 mg/day (p=0.1). Forty-one patients were retreated with rituximab. Four infusion reactions and one delayed serum sickness-like disease resulted in rituximab discontinuation. Three serious infections (1.3/100 patient-years) and two cancer-related deaths occurred. Conclusions: In common practice, the use of rituximab in pSS is mostly restricted to patients with systemic involvement. This prospective study shows good efficacy and tolerance of rituximab in patients with pSS and systemic involvement.